2017
DOI: 10.1007/s00411-017-0708-3
|View full text |Cite
|
Sign up to set email alerts
|

The influence of radiotherapy on ceruloplasmin and transferrin in whole blood of breast cancer patients

Abstract: Ceruloplasmin and transferrin are proteins which play a potential role in the process of breast cancer development. These molecules contain Cu2+ (ceruloplasmin) or Fe3+ ions (transferrin) and thus constitute paramagnetic centers, which can be studied using electron paramagnetic resonance method. The aim of the study was to determine how paramagnetic centers in whole blood of breast cancer patients change under the influence of radiation therapy. Samples of whole blood were taken from 17 women with breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Ceruloplasmin levels were corelated with tumor burden (10). A recent study showed that ceruloplasmin and transferine are increased in patients with breast cancer after radiotherapy (19). The extension of the degradation of proteins is at a much less scale, and it takes time to be activated so the thiols were not so elevated.…”
Section: Discussionmentioning
confidence: 99%
“…Ceruloplasmin levels were corelated with tumor burden (10). A recent study showed that ceruloplasmin and transferine are increased in patients with breast cancer after radiotherapy (19). The extension of the degradation of proteins is at a much less scale, and it takes time to be activated so the thiols were not so elevated.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular iron export is mediated by ferroportin (FPN) [ 65 ]. FPN exports Fe 2+ to the extracellular space where it is oxidized by ceruloplasmin (CP) [ 66 ], hephaestin (HEPH) [ 67 ], and zyklopen (HEPHL1) [ 66 ]. FPN is expressed in numerous cell types, in particular, in those involved in the regulation of plasma iron levels, such as enterocytes, macrophages, and hepatocytes [ 68 ].…”
Section: Intracellular Iron Metabolismmentioning
confidence: 99%
“…Ceruloplasmin loss-of-function is involved in neurodegenerative syndrome, whereas high ceruloplasmin level is associated with copper toxicity, Alzheimer's disease and cardiovascular diseases 43,44 . As ceruloplasmin levels were significantly high in cancer, ceruloplasmin has been suggested to be potential biomarkers in numerous solid tumors [45][46][47][48][49][50] . The relationship between ceruloplasmin level and bladder cancer has not been documented previously.…”
Section: Healthy Controls Lg Tumoursmentioning
confidence: 99%